Specific Instagram Works - Maćkowiak, Jagoda (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2024)
Universal access to social media platforms, the vast number of users, and the resulting diversity of published content have created challenges regarding the recognition of materials as subject matter of copyright and the protection of users’ creativity on these platforms. Within the legal publishing market, there is a noticeable lack of comprehensive consideration of the issues surrounding creative works on Instagram. Therefore, the aim of this article is to provide a legal analysis of the aforementioned issue and to examine the specific types of content shared by Instagram users based on existing concepts and institutions of copyright law. To achieve this, the article assesses the potential recognition of Instagram users as authors and explores whether materials posted on Instagram may constitute subject matter of copyright.